Atomically dispersed antimony on carbon nitride for the artificial photosynthesis of hydrogen peroxide - Teng, Zhenyuan (2023)
Artificial photosynthesis offers a promising strategy to produce hydrogen peroxide (H2O2)—an environmentally friendly oxidant and a clean fuel. However, the low activity and selectivity of the two-electron oxygen reduction reaction (ORR) in the photocatalytic process greatly restricts the H2O2 production efficiency. Here we show a robust antimony single-atom photocatalyst (Sb-SAPC, single Sb atoms dispersed on carbon nitride) for the synthesis of H2O2 in a simple water and oxygen mixture under visible light irradiation. An apparent quantum yield of 17.6% at 420 nm together with a solar-to-chemical conversion efficiency of 0.61% for H2O2 synthesis was achieved. On the basis of time-dependent density function theory calculations, isotopic experiments and advanced spectroscopic characterizations, the photocatalytic performance is ascribed to the notably promoted two-electron ORR by forming μ-peroxide at the Sb sites and highly concentrated holes at the neighbouring N atoms. The in situ generated O2 via water oxidation is rapidly consumed by ORR, leading to boosted overall reaction kinetics. [Figure not available: see fulltext.]